Peran Validitas dan Rehabilitas Dalam Evaluasi Pembelajaran - Buka, Nurhan; Jayamin, Mutiah Ayu; Kholis, Nur; N, Nursalam; Rasyid, Nur Akbar (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study discusses validity and rehabilitation. Validity and reliability are two important aspects in learning evaluation that complement each other. Validity ensures that the assessment tool actually measures the intended competency or ability, while reliability ensures that the assessment results are consistent and stable over time, between assessors, and between question forms. Valid assessments represent learning content and are relevant to the objectives to be achieved, while reliable assessments produce reliable data as a basis for decision making. Without validity, assessments become irrelevant. Without reliability, assessment results cannot be relied on. Therefore, in learning practices, teachers must ensure that the evaluation instruments used have high validity and reliability so that the assessment process is objective, fair, accurate, and truly reflects students' actual abilities.